Indigenous approaches to housing-induced domestic conflict management in Ondo City, Nigeria (2014)
This paper presents the results of a questionnaire survey of households and housing facilities carried out in 2007 in six wards of Ondo city in Ondo State of Nigeria. A total of 421 (2.39%) residential buildings were sampled. The study revealed that domestic conflict occurs most in tenement buildings where residents have to share facilities and amenities. This paper examines the nature, causes, and consequences of domestic conflict among residents and the methods of resolving such conflicts. It argues that indigenous strategies of conflict management work best in traditional societies and advocates their application in settlements with similar indigenous culture.